PEMBERDAYAAN MASYARAKAT MELALUI PENERAPAN TEKNOLOGI ECO-PAVING BLOCK - Jack Widjajakusuma; Aazokhi Waruwu; Priskila Christine Rahayu; Kevin Aprilio Wibowo (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Plastic waste poses significant social, economic, and environmental challenges as it decomposes over decades or even centuries. One potential solution is processing plastic waste into eco-paving blocks, which serve as eco-friendly alternative building materials while creating business opportunities. This Community Service Program (PkM) involved the Community Empowerment Institute of Bencongan Indah, Kelapa Dua District, Tangerang Regency. Activities included socialization and hands-on training on producing eco-paving blocks. The socialization covered the importance of plastic waste management, its health risks, and techniques for processing it into eco-paving blocks. Training aimed to improve partners’ knowledge and skills, evaluated through performance outcomes and pre- and post-activity questionnaires. Results showed strong community engagement and government support. Furthermore, the training significantly enhanced participants’ competence, as reflected in their improved ability to produce eco-paving blocks and higher scores in questionnaires after the program. Overall, this activity demonstrated that community-based education and training can effectively empower local stakeholders to transform plastic waste into valuable, sustainable products